-(8y+5)-(-7y-6t)=-1

Simple and best practice solution for -(8y+5)-(-7y-6t)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+5)-(-7y-6t)=-1 equation:


Simplifying
-1(8y + 5) + -1(-7y + -6t) = -1

Reorder the terms:
-1(5 + 8y) + -1(-7y + -6t) = -1
(5 * -1 + 8y * -1) + -1(-7y + -6t) = -1
(-5 + -8y) + -1(-7y + -6t) = -1

Reorder the terms:
-5 + -8y + -1(-6t + -7y) = -1
-5 + -8y + (-6t * -1 + -7y * -1) = -1
-5 + -8y + (6t + 7y) = -1

Reorder the terms:
-5 + 6t + -8y + 7y = -1

Combine like terms: -8y + 7y = -1y
-5 + 6t + -1y = -1

Solving
-5 + 6t + -1y = -1

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 6t + 5 + -1y = -1 + 5

Reorder the terms:
-5 + 5 + 6t + -1y = -1 + 5

Combine like terms: -5 + 5 = 0
0 + 6t + -1y = -1 + 5
6t + -1y = -1 + 5

Combine like terms: -1 + 5 = 4
6t + -1y = 4

Add 'y' to each side of the equation.
6t + -1y + y = 4 + y

Combine like terms: -1y + y = 0
6t + 0 = 4 + y
6t = 4 + y

Divide each side by '6'.
t = 0.6666666667 + 0.1666666667y

Simplifying
t = 0.6666666667 + 0.1666666667y

See similar equations:

| (20x+12y)(900)=12800 | | 3y^6-3y^3=0 | | 9x+x^2=-14 | | x(x)+2x-24= | | -(5y+1)-(-4-3)=0 | | 32y^9+4y^4= | | 4x^2+144=0 | | 6w^2+23w+20=0 | | 2x^2+13x+16=-5 | | 3x=(4)+(x-2) | | 2(9-5)-(3a+1)=0 | | ax+ay=a(x+y) | | 4x^2-12=13 | | 2/3n-5/8-2 | | 12(3x-1)=3(12x+6) | | 6+3r-3=8r+11-4r | | 4(7-2)= | | log(4x)+log(9x)=2 | | 4x-2(x-1)+5= | | 2r^3+14r^2-36r=0 | | 2x-5*(x+3*(3-x))= | | 7x-12-12x= | | 5(x-6)=55/11 | | -12.4=19.1+n/-7.9 | | n+3n+4n=100 | | 2w+2(w+10)=28 | | x+4x=258 | | 5640/9.4 | | 18p-45=o | | In(x+2)+in(x-2)=7 | | 3x+x=360 | | In(x)+in(x+1)=2 |

Equations solver categories